Nivel socioeconómico y cultural de los estudiantes de la Carrera de Odontología de la Universidad Nacional de Loja y su relación con el estado de salud bucodental, periodo octubre - marzo 2018 - Aguilar Ochoa, Diego René (2018)
One of the biggest problems that affects people worldwide is the economic crisis, living in poor conditions and limited in things regarded to health being one of the main risk factors. This is why the development of the following investigation has its objective to identify the socioeconomic and cultural from Dentistry students from the National University of Loja “UNL” and its relationship with dental health, a correctional study was performed, being the population studied of 230 students, which a survey was applied in order to find out about the socioeconomic and cultural, also the health clinic history, whose results were proved through an statistic test of squared Chi of Pearson. The pathologies with a high frequency found were cavity, periodontal illness, bad tooth position and par functional habits: from which cavity, periodontal illness, bad tooth position and par functional habits have a direct relationship with the socioeconomic and cultural situation from student with a higher significant level of 0,0 from the statistic test of squared Chi of Pearson respectively. Related to the par functional habits it was determined with a significant level of 0,4 which it doesn’t exist an influence between the socioeconomic and cultural level with the state of dental health. Keywords: Socioeconomic and cultural levels, dental health